The Loroxanthin Cycle: A New Type of Xanthophyll Cycle in Green Algae (Chlorophyta) - van den Berg, Tomas E.; Croce, Roberta (Frontiers in Plant Science, 2022)
Xanthophyll cycles (XC) have proven to be major contributors to photoacclimation for many organisms. This work describes a light-driven XC operating in the chlorophyte Chlamydomonas reinhardtii and involving the xanthophylls Lutein (L) and Loroxanthin (Lo). Pigments were quantified during a switch from high to low light (LL) and at different time points from cells grown in Day/Night cycle. Trimeric LHCII was purified from cells acclimated to high or LL and their pigment content and spectroscopic properties were characterized. The Lo/(L + Lo) ratio in the cells varies by a factor of 10 between cells grown in low or high light (HL) leading to a change in the Lo/(L + Lo) ratio in trimeric LHCII from .5 in low light to .07 in HL. Trimeric LhcbMs binding Loroxanthin have 5 ± 1% higher excitation energy (EE) transfer (EET) from carotenoid to Chlorophyll as well as higher thermo- and photostability than trimeric LhcbMs that only bind Lutein. The Loroxanthin cycle operates on long time scales (hours to days) and likely evolved as a shade adaptation. It has many similarities with the Lutein-epoxide – Lutein cycle (LLx) of plants.